The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1080/21645515.2021.1959148
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial assessing the efficacy, immunogenicity, and safety of vaccination with live attenuated varicella zoster virus-containing vaccines: ten-year follow-up in Russian children

Abstract: In Russia, a universal varicella vaccination (UVV) program has not been implemented, and varicella vaccination coverage is low. We assessed the efficacy, antibody persistence, and safety of one- and two-dose varicella vaccination schedules in Russian children with a ten-year follow-up period, as part of an international phase IIIB, observer-blind, randomized, controlled trial (NCT00226499). Children aged 12–22 months were randomized (3:3:1) to receive two doses of tetravalent measles-mumps-rubella-varicella va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
1
0
3
Order By: Relevance
“…Varicella vaccine has proven to be effective vaccine with a significant impact on varicella disease and complications and studies comparing immunogenicity of varicella vaccines compared to tetravalent varicella-measles-mumps-rubella vaccine found that anti-VZV antibodies were detected in 89.7% in recipient of varicella vaccine compared to 99.4% in recipients of trivalent vaccine ( 29 ). Furthermore, since the duration of immunity induced by vaccine is not clearly defined compared to natural immunity, a study on 10,000 US air force recruits found that anti-VZV IgG seropositivity was higher in recruits with history of natural varicella infection (95.4%) compared to vaccine recipients (72.4%) and that the odds of seropositivity is 24% less in vaccinee compared to those with natural immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Varicella vaccine has proven to be effective vaccine with a significant impact on varicella disease and complications and studies comparing immunogenicity of varicella vaccines compared to tetravalent varicella-measles-mumps-rubella vaccine found that anti-VZV antibodies were detected in 89.7% in recipient of varicella vaccine compared to 99.4% in recipients of trivalent vaccine ( 29 ). Furthermore, since the duration of immunity induced by vaccine is not clearly defined compared to natural immunity, a study on 10,000 US air force recruits found that anti-VZV IgG seropositivity was higher in recruits with history of natural varicella infection (95.4%) compared to vaccine recipients (72.4%) and that the odds of seropositivity is 24% less in vaccinee compared to those with natural immunity.…”
Section: Discussionmentioning
confidence: 99%
“…10 Na Rússia, em 2019, foram determinadas taxas de incidência de 559,1 casos de varicela por 100.000 habitantes, valor inferior ao reportado em Portugal. 6,11 Este caso alerta-nos para a pertinência da avaliação do estado de imunidade ao VVZ numa consulta de pré--conceção, que não se encontra preconizada no Programa Nacional para a Vigilância da Gravidez de Baixo Risco, da Direção-Geral da Saúde. 12 Neste caso, essa avaliação foi realizada após o relato de contacto significativo com o VVZ, onde a utente referiu desconhecer história prévia de varicela ou zona.…”
Section: Comentáriounclassified
“…De destacar a importância desta avaliação, particularmente às mulheres originárias de países onde as taxas de imunidade são inferiores às da população portuguesa. 7,[10][11] Na consulta de pré-conceção de mulheres imigrantes deve ser considerada a taxa de imunidade ao VVZ do país de origem, se conhecida, identificando-se assim as mulheres em maior risco de infeção por VVZ durante a gravidez. [10][11] Nestas é fundamental aferir o estado de imunidade, investigando a história de infeção prévia ou registo de va-cinação completa contra o VVZ; 18 muitas vezes a ausência de registos em imigrantes será um desafio e, caso exista dúvida quanto ao estado de imunização, será particularmente importante propor a avaliação serológica com a requisição de IgG e IgM para o VVZ, dada a probabilidade de imunidade ser inferior.…”
Section: Comentáriounclassified
See 1 more Smart Citation